Kolaborasi Internasional Antara Unimap Dan Fakultas Teknik Uisu Dalam Pendidikan Dan Pelatihan Teknis Dan Kejuruan Berbasis Pengabdian Masyarakat - Masri, Mahrizal; Parinduri, Luthfi; Widya, Helma; Alam, Hermansyah; Arifah, Rena (Jurnal Masyarakat Indonesia (Jumas), 2025)
The international collaboration between the TVET Center of Universiti Malaysia Perlis (UniMAP) and the Faculty of Engineering, Universitas Islam Sumatera Utara (FT-UISU) aims to strengthen ASEAN regional synergy through a Technical and Vocational Education and Training (TVET)-based community service program. This initiative focuses on empowering local communities through technical training relevant to industry needs while fostering stronger connections between academia, industry, and society. Key programs include training in 3D design, digital printing, and workshops on basic automation and the Internet of Things (IoT). The collaboration not only enhances local skills but also broadens the international academic networks of both institutions, contributing to the achievement of Sustainable Development Goals (SDGs). Challenges such as differences in curriculum systems and cross-border logistics were successfully overcome through intensive communication and shared commitment. Moving forward, both institutions aim to expand this collaboration through the development of joint TVET curricula, student and faculty mobility, and community-based research projects.